Uptake of diabetes follow-up checks by minority community groups: a rapid review of the evidence for the CYMELL study - Alison Porter (The Lancet, 2023)
Type 2 diabetes is a public health priority for the UK. A growing body of evidence has indicated ethnic and socioeconomic disparities in rates of diabetes prevalence and complications. Attendance at diabetes follow-up checks is key to ensuring complications are identified and managed at an early stage. The aim of this rapid review was to identify and summarise evidence of ways to improve diabetes management in ethnic minority groups.